Shelf Life Potential and the Fruit Cuticle: The Unexpected Player - Lara, Isabel; Heredia, Antonio; Domínguez, Eva (Frontiers in Plant Science, 2019)
The plant cuticle is an extracellular barrier that protects the aerial, non-lignified parts of plants from the surrounding environment, and furthermore plays important functions in organ growth and development. The role of the cuticle in postharvest quality of fruits is a topic currently driving a lot of interest since an increasing bulk of research data show its modulating influence on a number of important traits determining shelf life and storage potential, including water transpiration and fruit dehydration, susceptibility to rots, pests and disorders, and even firmness. Moreover, the properties of fruit cuticles keep evolving after harvest, and have also been shown to be highly responsive to the external conditions surrounding the fruit. Indeed, common postharvest treatments will have an impact on cuticle integrity and performance that needs to be evaluated for a deeper understanding of changes in postharvest quality. In this review, chemical and biophysical properties of fruit cuticles are summarized. An overview is also provided of postharvest changes in cuticles and the effects thereupon of some postharvest procedures, with the purpose of offering a comprehensive summary of currently available information. Identification of natural sources of variability in relevant quality traits would allow breeding for the improvement of postharvest life of fruit commodities.